Spatially-controlled NiCo2O4@MnO2 core–shell nanoarray with hollow NiCo2O4 cores and MnO2 flake shells: an efficient catalyst for oxygen evolution reaction. (15th May 2018) - Xue, Hairong; Yu, Hongjie; Li, Yinghao; Deng, Kai; Xu, You; Li, Xiaonian; Wang, Hongjing; Wang, Liang
Abstract: Control of structures and components of the nanoarray catalysts is very important for electrochemical energy conversion. Herein, unique NiCo2 O4 @MnO2 core–shell nanoarray with hollow NiCo2 O4 Cores and MnO2 flake shells is in situ fabricated on carbon textile via a two-step hydrothermal treatment followed by a subsequent annealing. The as-made nanoarray is highly active and durable catalyst for oxygen evolution reaction in alkaline media attribute to the synergetic effect derived from spatially separated nanoarray with favorable NiCo2 O4 and MnO2 compositions.